Penerapan Prosedur Audit Atas Persediaan Dalam Kegiatan Stock Opname Kantor Akuntan Publik (KAP) - Nayla Fadhlika Rizqi; Endah Susilowati (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to find out which implementation of audit procedures for inventory in stock taking activities is in accordance with the audit standards set by the Indonesian Institute of Public Accountants (IAPI). The BC Public Accounting Firm (KAP) is an audit service provider office. The method used in this research is a qualitative descriptive method. Researchers use data collection techniques through observation, literature study and documentation. The data source used in this research is secondary data. The results of this research indicate that the inventory audit procedures in stock taking activities carried out by the KAP BC auditor team are in accordance with the previously designed audit program. The procedures for carrying out audits of financial reports at the BC Public Accounting Firm are in accordance with auditing standards set by the Indonesian Institute of Public Accountants (IAPI). The procedure consists of planning, preparation, implementation, checking the final inventory list, reviewing inventory checks, final results of opname, and stock adjustments